2020
DOI: 10.1021/acs.bioconjchem.0c00494
|View full text |Cite
|
Sign up to set email alerts
|

Induced Disassembly of a Virus-like Particle under Physiological Conditions for Venom Peptide Delivery

Abstract: Virus-like nanoparticles (VLPs) show considerable promise for the in vivo delivery of therapeutic compounds such as bioactive venom peptides. While loading and targeting protocols have been developed for numerous VLP prototypes, induced disassembly under physiological conditions of neutral pH, moderate temperature, and aqueous medium, remain a challenge. Here, we implement and evaluate a ring-opening metathesis polymerization (ROMP) general mechanism for controllable VLP disassembly that is independent of cell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Therefore, the retention of SP variants on the VLP interior is dependent on the particle morphology, which determines whether the putative binding sites are accessible and whether the capsid pore size is large enough to allow cargo passage through the capsid wall [ 13 ]. Other studies have developed different strategies for the release of cargo, such as exploiting the environmental pH to induce disassociation from the VLP structure and exit [ 9 , 12 ] or the programmed particle disassembly [ 76 , 77 ]. The vast array of methods for the internalization of cargo makes the varied types of molecules possible, which in turn makes the equally astounding number of applications possible, some of which are summarized in Table 1 .…”
Section: Cargo Loadingmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, the retention of SP variants on the VLP interior is dependent on the particle morphology, which determines whether the putative binding sites are accessible and whether the capsid pore size is large enough to allow cargo passage through the capsid wall [ 13 ]. Other studies have developed different strategies for the release of cargo, such as exploiting the environmental pH to induce disassociation from the VLP structure and exit [ 9 , 12 ] or the programmed particle disassembly [ 76 , 77 ]. The vast array of methods for the internalization of cargo makes the varied types of molecules possible, which in turn makes the equally astounding number of applications possible, some of which are summarized in Table 1 .…”
Section: Cargo Loadingmentioning
confidence: 99%
“…Modifications on the structure can also be used to develop new strategies to bypass issues commonly encountered in development, such as the delivery of cargo. The incorporation of activated 5-Norbornene-2-carboxylic acid into the exterior of the P22 VLP for the programmed release of cargo under physiological pH has already been reported [ 76 , 77 ].…”
Section: Modification and Decoration Of The External Surface Of P22 Vlpmentioning
confidence: 99%
See 2 more Smart Citations
“…Kelly et al demonstrated the use of ring-opening metathesis polymerization (ROMP) for capsid disassembly. (Kelly et al, 2021) First, the P22His6GFP was functionalized on the surface-exposed lysine residues with 5-norbornene-2-carboxylic acid using EDC and sulfo-NHS coupling. Aqua-Met-a ruthenium-based ROMP catalyst-was added for ROMP initiation and subsequent capsid disassembly.…”
Section: P22mentioning
confidence: 99%